BUSINESS INTELLIGENCE CAPABILITIES AND ECONOMIC PERFORMANCE: SERIAL MEDIATION OF KNOWLEDGE ABSORPTIVE CAPACITY AND INNOVATION - Anjaningrum, Widiya Dewi; Santoso, Risa; Viloria, Vivien Amor; Cucio, Janice Soro; Aqromi, Nur Lailatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Numerous studies have delved into the performance of SMEs. In contrast, the intricate interplay between Business Intelligence Capabilities, Knowledge Absorptive Capacity, Innovation, and the Economic Performance of SMEs in Indonesia's creative economy remains unexplored, making this research a unique and significant contribution to the field. This research not only uncovers the serial mediating role of Knowledge Absorptive Capacity and Innovation in the relationship between Business Intelligence Capabilities and Economic Performance, but also provides practical insights for the 210 creative-economy-based SMEs in East Java, Indonesia. The findings suggest that enhancing Business Intelligence Capabilities can lead to increased knowledge absorptive capacity, innovation and economic performance, highlighting the potential for these SMEs to improve their business strategies. The theoretical implications of this research open the boundaries of Resource-based and Knowledge-based theory of the firm in the context of creative economy-based SMEs in developing countries that SMEs can already carry out simple business intelligence with existing resources. Future research needs to investigate qualitatively to what extent SMEs in the Society 5.0 era carry out Business Intelligence practices and how deep the absorption of knowledge is so that it can produce innovation that is out of the box.